Teknik Kontrak Perilaku untuk Mengurangi Perilaku Agresif Non Verbal pada Siswa Sekolah Menengah Atas - Ridwan Syahran; Mardi Lestari; Azam Arifyadi (ILIN Institute, 2020)
The general problem of this research is the non-verbal aggressive behavior of students in high school. Objectives of this research; 1) Knowing the general description of the level of non-verbal aggressive behavior in high school students; 2) Applying the behavioral contract technique to reduce non-verbal aggressive behavior in high school students. This research uses a quasi-experimental non-equivalent group design. The research subjects were students at Madani Senior High School in the city of Palu. Selection subjects using purposive sampling. Collecting data using a questionnaire Likert scale. The results showed that the average score of non-verbal aggressive students at the pretest was 100.98 in the high category, while in the posttest the average score of students' aggressiveness was 72.9 in the medium category. The condition after the implementation of the research showed a decrease in the level of non-verbal aggression in high school students after being given the behavior contract technique treatment.